2019
DOI: 10.1111/hsc.12743
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for psychosocial rehabilitation services in the Lisbon Metropolitan Area: A qualitative approach

Abstract: In Portugal, a mental health reform process is in place aiming to redefine the model of service provision. In 2008, a National Mental Health Plan (NMHP) was approved to provide policy guidance over the transition period. The NMHP intended, among others, to develop community-based services, with a specific focus on rehabilitation and deinstitutionalization. This study aims to explore the perspectives of service managers of psychosocial rehabilitation services regarding the main challenges to support the communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…There is also the implementation of the weak ICMHC Network due to heterogeneity in access and provision of psychosocial rehabilitation care. 16,27 This network is still in a pilot project phase and is therefore not available to all severely mentally ill patients with psychosocial disability. Continuity of care is therefore at risk due to the absence of a continuing care network that responds to LMHS needs.…”
Section: Methods Objectivementioning
confidence: 99%
See 1 more Smart Citation
“…There is also the implementation of the weak ICMHC Network due to heterogeneity in access and provision of psychosocial rehabilitation care. 16,27 This network is still in a pilot project phase and is therefore not available to all severely mentally ill patients with psychosocial disability. Continuity of care is therefore at risk due to the absence of a continuing care network that responds to LMHS needs.…”
Section: Methods Objectivementioning
confidence: 99%
“…There are 15 documents [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] that allow the definition of health care after discharge from psychiatric hospitalization in relation to what is foreseen in official documents, but also evidenced in practice.…”
mentioning
confidence: 99%
“…Although D City has achieved certain results in community mental health services, there are still some weak links, such as incomplete construction of basic facilities for community mental health services, need to strengthen investment in mental health services, and the mismatch between "software" and "hardware" in mental health services; The management mechanism of community mental health services is not clear, and the demand and supply of residents' mental health services are imbalanced; The quality of community mental health service teams and professionals needs to be improved, and so on. Szabzon found that the development of mental health reform has ensured significant changes in service delivery, and community mental health organizations are important participants in providing services [4].A community is a place where residents live and engage in long-term activities. Providing mental health services in the community is faster and more convenient, especially in case of sudden crisis events.…”
Section: 1the Necessity Of Strengthening the Construction Of Communit...mentioning
confidence: 99%